The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017 IEEE Conference on Computer Vision and Pattern Recognition Workshops (CVPRW) 2017
DOI: 10.1109/cvprw.2017.264
|View full text |Cite
|
Sign up to set email alerts
|

PETS 2017: Dataset and Challenge

Abstract: This paper describes the dataset and vision challenges that form part of the PETS 2014 workshop. The datasets are multisensor sequences containing different activities around a parked vehicle in a parking lot. The dataset scenarios were filmed from multiple cameras mounted on the vehicle itself and involve multiple actors. In PETS2014 workshop, 22 acted scenarios are provided of abnormal behaviour around the parked vehicle. The aim in PETS 2014 is to provide a standard benchmark that indicates how detection, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Some of the datasets were constructed with surveillance as their main purpose. The PETS 2017 dataset [83] contains data from on-board surveillance systems intended to protect critical assets. PETS stands for performance evaluation of tracking and surveillance, and its application is intended to evaluate the performance and detection of various surveillance events.…”
Section: Surveillancementioning
confidence: 99%
“…Some of the datasets were constructed with surveillance as their main purpose. The PETS 2017 dataset [83] contains data from on-board surveillance systems intended to protect critical assets. PETS stands for performance evaluation of tracking and surveillance, and its application is intended to evaluate the performance and detection of various surveillance events.…”
Section: Surveillancementioning
confidence: 99%
“…As a preliminary handling or first-order approximation in the current calculation, a simple but typical surveillance scenario of which interaction between targets is ignored. The second portion of risk entropy, S 2 , calculated only by Equation (8) or (9). Under a constraint of time and space, probability of security events of all moving targets, i.e., P M is regarded as a constant, so the risk entropy described by Equation ( 9) is:…”
Section: ) Calculation Of Smentioning
confidence: 99%
“…The state of art CV algorithm can integrate multiple views image and multiple types of information for target detection and identity recognition, behavior understanding, and many other tasks [6]- [8]. Evaluation of CV algorithms is fruitful, and many academic conferences with significant impact have launched several regular competitions on image/video analysis such as PETS [9], TRECVID [10], PascalVOC [11] and ImageNet Large Scale Visual Recognition Challenge (ILSVRC) [12]. These research works have shown how the image detail affects the performance of the CV algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several challenges in the area of activity recognition including [19,26,10,23]. The focus is on classification or recognition in short untrimmed video segments.…”
Section: Activity Detectionmentioning
confidence: 99%